Benchmarking Australian Dental Weighted Activity Units against public and private dental fee schedules: a cross-sectional item-code comparator study - Jonathon Oddy; William Ha (BDJ Open, 2026)
Abstract Objective To benchmark Dental Weighted Activity Units (DWAUs) against Australian dental remuneration schedules and derive suggested recalibration factors for endodontics, periodontics and prosthodontics. Materials and methods A cross-sectional item-code comparator study linked Australian Dental Association item codes to DWAU values and fees from public and private schedules, standardised to 1 January 2025 Australian dollars. The primary outcome was grouped DWAU per dollar, calculated as the sum of DWAUs divided by the sum of fees and expressed as DWAU per $1000. Lower values indicated fewer DWAUs credited per dollar of remuneration. Merged general and merged specialist fee series were constructed, with bootstrap 95% confidence intervals and suggested stream-specific calibration factors estimated. Results Of 343 item codes, 264 had DWAU values greater than zero and 260 were included. Overall DWAU per $1000 was 1.589 for merged general comparators and 1.130 for merged specialist comparators. Under specialist comparators, endodontics had the lowest value at 0.945 DWAU per $1000, 16.40% below the benchmark. The suggested specialist calibration factor for endodontics was 1.196. Discussion The findings indicate that current DWAU values are not uniformly aligned with remuneration signals, particularly for specialist endodontics, and supports stream-specific review rather than a single uniform adjustment. Conclusions Cross-schedule benchmarking and specialist-adjusted DWAU rates may improve public dental activity measurement, commissioning and specialist service planning.